Older kidney transplantation candidates’ expectations of improvement in life and health following kidney transplantation: semistructured interviews with enlisted dialysis patients aged 65 years and older - Lønning, Kjersti (BMJ Open, 2018)
OBJECTIVE: The aim was to study the expectations of improvement in life and health following kidney transplantation (KTx) in a population of wait-listed patients ≥65 years with end-stage kidney disease. DESIGN: Qualitative research with individual in-depth interviews. SETTING: Patients on dialysis enlisted for a KTx from a deceased donor were included from an ongoing study of older patients’ perspectives on KTx. Qualitative face-to-face interviews were conducted in a safe and familiar setting, and were analysed thematically using the theoretical framework of lifespan. INFORMANTS: Fifteen patients (median age 70 years, range 65–82) from all parts of Norway were interviewed. Informants were included consecutively until no new information was gained. RESULTS: Two main themes were evident: receiving a kidney is getting life back and grasp the chance. In addition, the themes ‘hard to loose capacity and strength’, ‘reduced freedom’ and ‘life on hold’ described the actual situation and thereby illuminated the informants’ expectations. The informants tried to balance positive expectations and realism towards KTx, and they were hoping to become free from dialysis and to live a normal life. CONCLUSION: This study shows that older KTx candidates comprise a heterogeneous group of patients who take individual approaches that allow them to maintain autonomy and control while waiting for a transplant. This study provides new knowledge about the older KTx candidates relevant for clinicians, patients and researchers.